Numerical study on a fully-prefabricated damage-tolerant beam to column connection for an earthquake-resilient frame. (15th March 2018) - Deng, Kailai; Wang, Tao; Kurata, Masahiro; Zhao, Canhui; Wang, Kangkang
Highlights: A novel beam to column connection was proposed to achieve damage tolerance in earthquake. A sophisticated numerical model is built in ABAQUS for parametric analysis. Seldom damage occurred on the composite UHPC joint under maximum considered earthquake. More than 80% external work was dissipated by the fiction damper. The design procedure for the fully prefabricated connection was provided. Abstract: Seismically resilient structures are appealing because any damage can be quickly repaired and the structures can soon be reoccupied. In the present paper, a novel fully-prefabricated beam to column connection was proposed. A composite ultra-high-performance concrete (UHPC) joint and a friction damper were employed to connect a beam to a column using the proposed joint. All components were connected using bolts, which are convenient for quick replacement. Under earthquake excitation, deformation was mainly concentrated in the friction damper. The composite UHPC joint sustained little or no damage, owing to its small section height and excellent crack resistance. Numerical analyses were conducted using commercial finite element software, ABAQUS, to obtain the seismic performance of the beam to column connection. The effects of various parameters of the composite UHPC joint and the friction damper were investigated. According to the analysis, the beam to column connection delivered satisfactory mechanical characteristics and damage tolerance. Detailed design suggestions for the beam to column connection are provided.